Initial treatment of presumed pacemaker or implantable cardioverter defibrillator malfunctions: algorithm and rationale - Matthias Mueller; Christoph Weiser; Michael Pfeffer; Thomas Mitteregger (Emergency Medicine Journal, 2026)
The increasing prevalence of permanent pacemakers (PPMs) and implantable cardioverter defibrillators (ICDs) has led to a rising number of device malfunctions, which can have painful or even life-threatening consequences. As device technology advances, emergency personnel frequently face uncertainty in the initial management of these complex patients, given limited access to device reprogramming or interrogation outside specialised cardiology settings. This paper presents practical algorithm-based approaches for the immediate treatment of presumed PPM and ICD malfunctions in the prehospital and emergency department setting to support timely effective emergency care until expert consultation is available.